Phenotypic Detection of Metallo-Beta-Lactamases in Carbapenem Resistant Acinetobacter baumannii Isolated from Pediatric Patients in Pakistan. (30th March 2016) - Anwar, Muneeza; Ejaz, Hassan; Zafar, Aizza; Hamid, Hamdan
Abstract : Multidrug resistant A. baumannii has emerged as an important and problematic human pathogen as it is the causative agent of several types of infections especially in neonates and immunocompromised patients because they have least capacity to fight against infections. Carbapenems are used as last resort antibiotics for treating these infections but currently resistance against carbapenems due to MBL production is on the rise. The objective of this study was to determine the frequency of antibiotic resistance in A. baumannii and also to compare the efficacy of combined disk test and double disk synergy test for detection of metallo-beta-lactamases. A total of 112 A. baumannii were identified from various clinical samples and antibiotic susceptibility profile was determined by Kirby-Bauer Disk Diffusion method. Out of 112, 66 (58.9%) isolates were resistant to both imipenem and meropenem (OXOID). These resistant isolates were tested for carbapenemase production, and 55 (83.3%) were carbapenemase producers by Modified Hodge Test. These isolates were further tested for MBL production by combined disk test and double disk synergy test. Out of 66, 49 isolates were positive by both methods, CDT and DDST, and only one isolate was detected as negative (with kappa value = 0.038). All MBL producing strains showed remarkable resistance to cephalosporins, fluoroquinolones, aminoglycosides, and piperacillin/tazobactam (OXOID). The antibiotic resistance was very high in A. baumannii which were isolated from children in Pakistan specially attending a nephrology unit.